Anticorpos contra o peptídeo sintético p314 derivado da proteína 1 de superfície de merozoíto de Plasmodium vivax (Pvmsp-1) como marcadores de exposição - Aline Marzano Miranda (2022)
Plasmodium vivax is the most widely distributed human plasmodium in the world and the most prevalent species in Brazil. About 99% of transmission occurs in endemic areas of the Brazilian legal Amazon, but there is also transmission in extra-Amazonian areas, whether autochthonous or imported, more precisely in Atlantic Forest regions. Biological characteristics of this species make it difficult to interrupt transmission: (i) early maturation of gametocytes, (ii) presence of intrahepatic hypnozoites, and (iii) asymptomatic or oligosymptomatic cases that maintain the transmission chain. Thus, the identification of specific P. vivax proteins that can serve as indicators of exposure to the parasite can be useful to delimit the transmission areas of this species, identify asymptomatic reservoirs and efficiently implement control measures such as diagnosis and treatment. specific treatment. Merozoite Surface Protein 1 (MSP-1) stands out as a possible target because it is essential for erythrocyte invasion by merozoites and has conserved and variable portions according to plasmodium species. Thus, the objective of this work was to evaluate the potential of antibodies against a peptide derived from P. vivax MSP-1 pre-selected by spot-synthesis, p314, as a potential serological biomarker of vivax malaria. This peptide was synthetically produced in soluble form and was used in ELISA tests to measure the response of specific antibodies (IgM, IgG and their subclasses) in plasma from infected patients with P. vivax (n= 220), infected patients with P. falciparum (n=15) and uninfected individuals never exposed to malaria (n=48). The results show that anti-p314 IgG levels were significantly higher in patients infected with P. vivax compared to those infected with P. falciparum (p=0.0001). To evaluate the kinetics of the IgM response, total IgG and subclasses, plasmas from 13 patients, obtained on the day of thick smear malaria diagnosis (D0) and 63 days after specific treatment for P. vivax, were used. There were no significant differences between the levels of IgM and IgG in relation to days 0 and 63. Among the subclasses, IgG1 stood out as a biomarker of exposure, since its levels were significantly higher in plasma from patients infected with P. vivax and IgG3 showed a significant drop in levels two months after the diagnosis of infection. These data are promising and suggest that the IgG1 anti-p314 subclass is a target marker of exposure by P. vivax, therefore, it may be a potential biomarker to be implemented in epidemiological studies aimed at delimiting areas of transmission. In addition, the evaluation of IgG1 anti-p314 associated with IgG3 could be used to estimate P. vivax outbreaks and recent exposures to this parasite.